ON THE PECULIARITIES OF TEACHING SPANISH PERSONAL PRONOUNS TO AN ARMENIAN-SPEAKING AUDIENCE - Saroyan, Lilit (Foreign Languages for Special Purposes, 2025)
This study is dedicated to the teaching of Spanish personal pronouns. The use of personal pronouns in Spanish often appears quite complex to Armenian learners, as well as to other foreigners studying Spanish. The article thoroughly examines modern teaching methods that contribute to the effective teaching, acquisition, and correct usage of Spanish personal pronouns. The relevance of this article is conditioned by the growing demand for the Spanish language worldwide and the increasing number of learners from various national backgrounds. The article addresses the main approaches that play a key role in teaching Spanish personal pronouns and, through a learner-centered approach, make the process of mastering them more accessible.